2008
DOI: 10.4049/jimmunol.181.5.3690
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Soluble TGF-β Receptor by Tumor Cells Enhances Dendritic Cell/Tumor Fusion Vaccine Efficacy

Abstract: Dendritic cell (DC)-based antitumor immunotherapy is a promising cancer therapy. We have previously shown that tumor-derived TGF-β limits the efficacy of the DC/tumor fusion vaccine in mice. In the current study we investigated the effect of neutralizing tumor-derived TGF-β on the efficacy of the DC/tumor fusion vaccine. An adenovirus encoding human TGF-β receptor type II fused to the Fc region of human IgM (Adv-TGF-β-R) or a control adenovirus encoding LacZ (Adv-LacZ) was used to express a soluble form of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…In this light, DC genetically engineered to secrete a VEGF/vascular permeability factor decoy receptor that neutralizes soluble VEGF and precludes signaling in DC resulted in increased expression of costimulatory molecules and proinflammatory cytokines/chemokines by DC and improved CTL activity and anti-tumor immune control in a murine colon cancer model (157). Similar improvements in the efficacy of an exogenous DC vaccine were observed following neutralization of tumor-derived TGFβ (158). Alternatively, other approaches for enhancing exogenous DC-induced anti-tumor immune responses aim at blocking either the immunosuppressive mediators expressed by tumor-altered DC or the targets of these mediators expressed on other immune cells.…”
Section: Immunotherapeutic Strategies For Interfering With Tumor-assomentioning
confidence: 65%
“…In this light, DC genetically engineered to secrete a VEGF/vascular permeability factor decoy receptor that neutralizes soluble VEGF and precludes signaling in DC resulted in increased expression of costimulatory molecules and proinflammatory cytokines/chemokines by DC and improved CTL activity and anti-tumor immune control in a murine colon cancer model (157). Similar improvements in the efficacy of an exogenous DC vaccine were observed following neutralization of tumor-derived TGFβ (158). Alternatively, other approaches for enhancing exogenous DC-induced anti-tumor immune responses aim at blocking either the immunosuppressive mediators expressed by tumor-altered DC or the targets of these mediators expressed on other immune cells.…”
Section: Immunotherapeutic Strategies For Interfering With Tumor-assomentioning
confidence: 65%
“…An adenovirus encoding human TGF-β receptor type II fused to the Fc region of human IgM was used to express a soluble form of the neutralizing TGF-β receptor (TGF-β-R), which has been shown to cross-react with mouse TGF-β [21]. We have previously demonstrated that the soluble TGF-β-R neutralizes TGF-β produced by tumor cells [22]. A CT26 cell line that hence produces below physiologic levels of TGF-β (CT26-TGF-β-R) was generated using a retrovirus that expressed TGF-β-R and the neomycin resistance gene.…”
Section: Methodsmentioning
confidence: 99%
“…This modified ELISA estimates the TGF-β-R concentration by measuring the amount of TGF-β bound to TGF-β-R, and has previously been described in further detail [22]. …”
Section: Methodsmentioning
confidence: 99%
“…A series of studies demonstrated the efficacy of autologous DCs pulsed with defined TAAs as therapeutic cancer vaccines in preclinical models (Sas et al , 2008; Zhang et al , 2008). Although not as effective as in preclinical models, DCs pulsed with TAAs were shown to induce durable anti-tumor responses with demonstrable clinical efficacy.…”
Section: Dendritic Cell-based Cancer Vaccinesmentioning
confidence: 99%